Epidemiology of Depression in Patients with Psoriasis: A Nationwide Population-based Cross-sectional Study - Stephen Chu-Sung Hu; Gwo-Shing Chen; Hung-Pin Tu (Medical Journals Sweden, 2019)
The epidemiology of depression in patients with psoriasis has not been well defined in the Asian population. This study evaluated the epidemiological features of, and risk factors for, depression among patients with psoriasis in Taiwan. A nationwide population-based cross-sectional study was undertaken using the National Health Insurance Research Database. This study included 17,086 patients with psoriasis and 1,607,242 patients from the general population. The prevalence of depression in patients with psoriasis was 11.52%, while the prevalence of depression in the general population was 7.73% (prevalence ratio 1.49, 95% confidence interval 1.43-1.55). Multivariable analysis showed that, in patients with psoriasis, risk factors associated with depression were: age 20-50 years, female sex, low income, and major comorbid diseases, including liver cirrhosis, renal disease, cardiovascular disease and cerebrovascular disease. Therefore, the prevalence of depression is higher in patients with psoriasis, particularly in young and middle-aged women with low income and major comorbidities.